Accelerated and field curing of bituminous roadbase - Chaddock, B.; Pledge, K.; Transport Research Laboratory (Great Britain) (Crowthorne, Berkshire TRL Limited, 1994)
The change in stiffness of bituminous roadbase and basecourse materials during their early life, or curing, was investigated as part of a research programme to aid the development of a performance specification based on structural properties. It was shown that significant curing can occur as a result of the hardening of the binder. Although curing was shown to be dependent on temperature and air voids content of the bituminous materials, compositional differences between materials could not account for the large variability in curing behaviour observed. Consequently, a study was undertaken to determine whether a simple laboratory accelerated curing test could be devised to predict the in-situ curing of bituminous materials. Results from a test that involves heating supported cores of bituminous materials in a forced air draft oven at 60 degrees C for 48 hours was found to correlate best with in-situ curing of trial pavements. Further information on this relationship for a wider range of materials and climatic conditions is required before the test can be incorporated in a performance based specification with confidence. The magnitude of curing observed to date has been demonstrated to be beneficial to the performance of the road. (A)
Keywords: Pavements, Bituminous; Pavements, Flexible